The chronicles of Fernão Lopes. - Lopes, Fernão, approximately 1380- (Colección Támesis. Textos, 2023)
Volume I of the first complete English translation of the chronicles of Fernão Lopes chronicles the reign of Pedro I (1357-67), dubbed both 'the Just' and 'the Cruel', including his dealings with the kingdom of Castile, the war between Castile and Aragon, and the revenge he took on the men who murdered the woman he loved, Inês de Castro.